Developing a Supportive Organisational Culture for Continuous Improvement in Manufacturing Firms in Saudi Arabia - Adel Algethami; Fadi Assad; John Patsavellas; Konstantinos Salonitis (Administrative Sciences)
Continuous improvement (CI) is vital for Saudi manufacturing firms to remain competitive in the global market. However, cultural factors significantly influence CI adoption. This qualitative study, involving 28 interviews and focus groups with employees from five local manufacturing firms, explored these factors. Seven key cultural themes emerged, including communication, employee wellbeing, talent management, ethics, top management support, organisational learning, and compliance. A conceptual framework was developed to assess a firm’s cultural proximity to an ideal CI state. This framework integrates a diagnostic tool to guide firms in evaluating their cultural landscape and implementing targeted interventions for successful CI adoption. Future research should explore the long-term impacts of cultural shifts on performance and competitiveness.